LA CADENA SER EN FACEBOOK: NUEVAS ESTRATEGIAS DE INTERACCIÓN CON LA AUDIENCIA - Fátima RAMOS DEL CANO (Fonseca, Journal of Communication, 2023)
The current news media context has consolidated social networks services as the new and decisive communication and interaction tools with users. In this regard, the purpose of this article is to analyze how the traditional audience participation has been affected by its implantation, focusing our inquiry on Facebook profile (being Facebook the network with the greatest audience in Spain and one of the most significant at the international level) of Cadena Ser news programmes: "A Vivir que son dos días", "Hora 25", "Hoy por Hoy" and "La Ventana".